Literacy Study on Governance, Risk and Compliance (GCR) and Performance - Maf'ul Taufiq (International Journal of Management, Economic and Accounting, 2023)
In this research explains and explains how the impact of the implementation of Governance, Risk, and Compliance (GCR) and its impact on company performance, researchers conduct theoretical studies and previous literature studies where the theory used is Agency Theory which concerns the occurrence of information asymmetry and through Stakeholder Theory which explains how the relationship between the company and stakeholders. Governance, Risk, and Compliance (GRC) information shown to company stakeholders. where the theory used will help in explaining how the impact of implementing Governance, Risk, and Compliance (GRC) can improve company performance. This study will also examine previous research that provides an overview of the Implementation of Governance, Risk, and Compliance (GRC) and its impact on company performance. This research uses a qualitative descriptive approach by conducting theoretical studies and literature studies by conducting literature studies and collecting journals through websites and the internet. The research methodology used is purely through the analysis of existing literature and theoretical studies related to the topics discussed in the research, then researchers discuss and provide an overview of conclusions through theoretical analysis and research results that support to obtain good theoretical research results related to the themes discussed in the research. Through the results of theoretical studies and literature studies, results were found with conclusions The implementation of companies that apply the concept of Governance, Risk, and Compliance (GRC) in an integrated manner, and in accordance with the provisions and systematically in a sustainable manner will increase coordination power in each line of the company and create efficiency in company management which will have an impact on company performance.